2012
DOI: 10.1017/s0960258512000219
|View full text |Cite
|
Sign up to set email alerts
|

A temperate rhamnaceous species with a non-enclosing stone and without physical dormancy

Abstract: The purpose of the present study was to investigate the dormancy break and germination requirements of seeds from the rhamnaceous vine Berchemia scandens. The fleshy fruit contains a two-locular stone with an endocarp described as ‘bony, thickish’. Scarified and non-scarified stones increased by about 30–50% in mass during imbibition over a 24-h period. The endocarp of the stone does not completely enclose the seeds and a soft tissue region is present. This region is the primary area of water entrance to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…In contrast, fresh seeds of B. scandens, C. laevigata, E. fortunei, J. virginiana, Lonicera japonica, P. quinquefolia and V. vulpina germinated to low percentages, but cold-stratified seeds to moderate to high percentages across the temperature range. The germination responses in other populations of these same species have also been found to improve with cold stratification (Hidayati et al 2000;Bonner & Karrfalt 2008;Walck et al 2012;Rounsaville et al 2018). Ligustrum sinense and Lonicera maackii produced seeds that were mostly non-dormant when freshgerminating to higher percentages than the other species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, fresh seeds of B. scandens, C. laevigata, E. fortunei, J. virginiana, Lonicera japonica, P. quinquefolia and V. vulpina germinated to low percentages, but cold-stratified seeds to moderate to high percentages across the temperature range. The germination responses in other populations of these same species have also been found to improve with cold stratification (Hidayati et al 2000;Bonner & Karrfalt 2008;Walck et al 2012;Rounsaville et al 2018). Ligustrum sinense and Lonicera maackii produced seeds that were mostly non-dormant when freshgerminating to higher percentages than the other species.…”
Section: Discussionmentioning
confidence: 97%
“… Stone consisted of two (inseparable) locules; a locule contained a seed or was empty (Walck et al 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of the Rhamnaceae have an investing embryo (Martin, 1946) and can be non-dormant or, following the dormancy classification system Baskin, 1998, 2004), show physiological (PD), physical dormancy (PY) or combined ( physical and physiological; PY + PD) dormancy. Physical dormancy is the most represented class in this family (61 % of the investigated species), followed by PY + PD (22 %), PD (12 %) and nondormancy (ND) (6 %; Walck et al, 2012). Mattana et al (2009) reported that germination of R. persicifolia seeds could be achieved, without any scarification, at warm temperatures (≥20 8C), excluding the presence of PY.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the pre-treatment method of filing should be improved so as to achieve a better germination rate. Seed coat impermeability is not the only cause for prolonged and low germination for B. discolour and it is recommended that the seeds be chopped at the radicle end followed by soaking in cold water and drying in the sun for 24 h as a method to promote germination (Walck et al, 2012). Majaju and Zananga (2006), working on indigenous tree species in Zimbabwe, germinated a variety of trees and observed varied germination rates.…”
Section: Introductionmentioning
confidence: 99%